The Translation Ideology of English Idiomatic Expressions in Temperatures Rising into Indonesian in Hasrat Membara - Maharani, Ida Ayu; Suardhana, I Wayan (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p19, 2018)
This paper entitled “The Translation Ideology of English Idiomatic Expressions in Temperatures Rising into Indonesian in Hasrat Membara” which discusses the use of translation technique, translation method and translation ideology of idiomatic expressions. The problems of the study mainly focuses on the types of translation technique, translation method and translation ideology found in the novel. The aims of this research are to find out the types of translation technique, translation method and translation ideology applied in both novels. The data are presented and explained based on theoretical framework. The data were taken from a novel written by Sandra Brown. The data were collected through documentation and observation. This study used descriptive qualitative method and applied the theory proposed by Molina and Albir (2002) to classify the types of translation technique, the theory proposed by Newmark (1988) to describe the types of translation method and the theory proposed by Hatim (2001) to find the ideology applied in the translated novel. Among twelve translation techniques, there are only five types of translation techniques found in the data of the novel namely variation, adaptation, description, deletion, and generalization. Based on the types of translation technique found, all of them are oriented towards the target language. Thus, the method used in the translated novel is communicative method which is oriented towards to the target language. Based on translation technique and method, it is concluded that the translated novel has a tendency to domestication ideology which is target language oriented.